LOCAL COMMUNITY EMPOWERMENT IN SUSTAINABLE TOURISM DEVELOPMENT IN SELO TOURISM VILLAGE, SELO DISTRICT, BOYOLALI REGENCY, CENTRAL JAVA - Andi Sujarwo; Ika Devy Pramudiana; Widyawati Widyawati; Ulul Albab (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2026)
Selo Tourism Village, located in Selo District, Boyolali Regency, holds significant potential to be developed as a sustainable tourism destination. This study aims to analyze the extent to which local community empowerment contributes to sustainable tourism development using Jim Ife's community empowerment theory. The focus of this study includes four main indicators: resources, opportunities, knowledge, and skills, as well as their impacts on economic, social, and environmental sustainability. This research adopts a qualitative method with a descriptive approach. Data were collected through in-depth interviews, direct observation, and documentation from key informants, including tourism managers, village authorities, and local communities. The findings indicate that the resource indicator has a success rate of 65%, particularly in increasing tourist visits and environmental awareness. The opportunity indicator achieved 60%, highlighting an increase in community participation in tourism activities, although technical training and job access still require improvement. The knowledge indicator reached 55%, especially in preserving local culture, though integrated marketing strategies need further development. Meanwhile, the skills indicator showed a success rate of 58%, with initial successes in digital promotion, but improvements in technological management and event organization are still needed. The study concludes that local community empowerment significantly impacts sustainable tourism development in Selo Tourism Village, despite areas requiring enhancement. Strategic recommendations include increasing resource allocation, providing more equitable training, and strengthening community capacity to professionally manage tourism potential. With these improvements, Selo Tourism Village holds great potential to become a leading tourism destination that supports community welfare, cultural sustainability, environmental preservation, and delivers positive economic impacts.